1986
DOI: 10.1128/jcm.24.5.840-843.1986
|View full text |Cite
|
Sign up to set email alerts
|

Modified selective medium for isolation of Campylobacter spp. from feces: comparison with Preston medium, a blood-free medium, and a filtration system

Abstract: 389-393, 1983) selective medium, consisting of cefoperazone (15 mg/liter), rifampin (10 mg/liter), colistin (10,000 IU/liter), and amphotericin B (2 mg/liter) (medium Ml), for the isolation of Campylobacter jejuni and Campylobacter coli from stool specimens was modified as follows: cefoperazone (30 mg/liter), rifampin (10 mg/liter), and amphotericin B (2 mg/liter) (medium M2). A comparative study of the isolation of Campylobacter spp. from stool specimens was carried out with medium Ml; medium M2; a selective … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
32
0
1

Year Published

1988
1988
2018
2018

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 77 publications
(34 citation statements)
references
References 18 publications
1
32
0
1
Order By: Relevance
“…Several methods are available to achieve an opti- (Agulla et al, 1987). For example, some strains of C. coli are sensitive to polymyxin B and may therefore be inhibited in Preston enrichment broth or Preston agar (Goossens et al, 1986),…”
Section: Non-food-associated Vectors and Sourcesmentioning
confidence: 99%
“…Several methods are available to achieve an opti- (Agulla et al, 1987). For example, some strains of C. coli are sensitive to polymyxin B and may therefore be inhibited in Preston enrichment broth or Preston agar (Goossens et al, 1986),…”
Section: Non-food-associated Vectors and Sourcesmentioning
confidence: 99%
“…In 1977, Skirrow [24] confirmed the findings of the Belgian team and described a simpler technique for culturing C. jejuni and C. coli from stool specimens, which allowed widespread isolation of these organisms. The later development of selective media, obviating the need to filter suspensions, brought the isolation of Campylobacter into the realm of routine microbiology [24][25][26][27][28][29][30]. Reports from industrialised countries, including European countries [19][20][21]24,[30][31][32][33], Canada [34] and the USA [35], and from developing countries, including Zaire [23] and Rwanda [36], have shown that Campylobacter enteritis occurs worldwide.…”
Section: The Breakthroughmentioning
confidence: 99%
“…jejuni and C. coli can be isolated easily from faeces by primary plating on selective media and incubation for 48-72 h at 42°C in a microaerobic atmosphere. A variety of selective media (bloodbased, blood-free charcoal-based) are available [24][25][26][27][28][29][30]. These contain antibiotics that suppress the normal bacterial enteric flora.…”
Section: I C R O B I O L O G Ymentioning
confidence: 99%
“…The persistence of non-jejuni species of thermophilic Campylobacter has received little attention from the scientific community, presumably because of the relatively low isolation rate of these species from surface waters (Bolton et al 1987). However, this may be as a consequence of the application of selective regimes inhibitory towards non-jejuni species (Goossens et al 1986). Under all imposed conditions, the overall decay rates of thermophilic non-jejuni isolates were more negative than those of Camp.…”
Section: ------------------------------------------------------------mentioning
confidence: 99%